The effect of beverage preparation method on aluminium content in coffee infusions - Franková, Adéla; Drábek, Ondrej; Havlík, Jaroslav; Száková, Jirina; Vanek, Ales (Journal of inorganic biochemistry, 2009)
Seven types of coffee were prepared by four methods. Three of them - simple coffee infusion, preparation in ibrick and moka pot - are very often used to prepare coffee at home. The fourth one - a single-cup filter is typical for Vietnam. Cookware used for each method was made from glass, aluminium, stainless steel and two types of alloys. Amounts of Al leaching to coffee infusions were determined. On average, the highest amount of Al was in coffee infusions brewed in aluminium single-cup filter, and the lowest in infusions prepared by simple extraction. Other brewing methods in combination with different tool materials resulted in similar Al content. The type of brewing method significantly influences the Al content in final infusion. Aluminium content varies in infusions in relation to the method of choice, especially when using single-cup filter. Despite the fact that coffee is considered to be a poor source of Al for humans, in some cases, Al content in infusions can even reach the values reported for tea infusions.
Keywords: Beverages; Food Contamination; Aluminum; Cooking and Eating Utensils; Food Handling; hliník; Coffee; nápoje; nádobí; kontaminace potravin; manipulace s potravinami; káva